2012
DOI: 10.1080/03235408.2012.677493
|View full text |Cite
|
Sign up to set email alerts
|

Effect of yellow rust on yield components of barley cultivars with race-specific and slow rusting resistance to yellow rust

Abstract: 2012) Effect of yellow rust on yield components of barley cultivars with race-specific and slow rusting resistance to yellow rust, Archives Of Phytopathology And Plant Protection, Yellow rust caused by Puccinia striiformis f. sp. hordei is an important disease of barley (Hordeum vulgare L.) in some parts of the world. We compared the effectiveness of different types of resistance in field plots at Ardabil Agricultural Research Station (Iran) during 2010-2011. Yield components along with slow rusting parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 26 publications
1
8
0
3
Order By: Relevance
“…Similarly, Safavi (2015) reported a TKW loss of 40.1% in the susceptible cultivar Morocco and a TW loss of 19% in susceptible genotypes (Everts et al 2001). The higher loss in TKW and TW reached 40.8 and 8.89% in Diyarbakır, 20.4 and 20.8% in Adıyaman, respectively.…”
Section: Effect Of Stripe Rust On Yield and Yield Componentsmentioning
confidence: 88%
See 1 more Smart Citation
“…Similarly, Safavi (2015) reported a TKW loss of 40.1% in the susceptible cultivar Morocco and a TW loss of 19% in susceptible genotypes (Everts et al 2001). The higher loss in TKW and TW reached 40.8 and 8.89% in Diyarbakır, 20.4 and 20.8% in Adıyaman, respectively.…”
Section: Effect Of Stripe Rust On Yield and Yield Componentsmentioning
confidence: 88%
“…The highest TKW and TW loss occurred in Nurkent, G3 and Karacada g-98 in both locations. Similarly, Safavi (2015) reported a TKW loss of 40.1% in the susceptible cultivar Morocco and a TW loss of 19% in susceptible genotypes (Everts et al 2001). Stripe and leaf rust decreased the photosynthesis area and consequently lowered the percentages of yield and yield components (Herrera-Foessel et al 2007).…”
Section: Effect Of Stripe Rust On Yield and Yield Componentsmentioning
confidence: 96%
“…The previous studies of Sharma-Poudyal and Chen (2011), Safar (2015) and Afzal et al (2007) reported that the stripe rust can cause approximately complete yield loss (100%) when severe infection occurs very early in the growth stage and the disease continues to develop under favorable environmental conditions, during the growing season. While, under Egyptian field conditions, Omara et al (2016) showed that the actual percentage loss in grain yield of some highly susceptible wheat cultivars ranged between 53.7 and 55.4%.…”
Section: Impact Of Stripe Rust Infection On Grain Yield Of the Testedmentioning
confidence: 98%
“…Her iki sezonda da % MR (Orta dayanıklı) ile 90S arasında değişmiş, genel olarak hassas olan çeşitler daha düşük tane verimine sahip olmuşlardır (Tablo 4). Benzer sonuçlar Aktaş (2014) tarafından belirtilmiş olup, yerel buğday çeşitlerinin yüz yıllar boyunca aynı çevrede yetiştirilmesi bazı sarı pas patotiplerine karşı hassas hale geldiği, başka bir ifade ile bu patotiplerin bu yerel buğdayların savunma mekanizmaları üzerinde uzmanlaştığı, fakat hastalık seyrinin bayrak yaprağı üzerinde gelişiminin yavaş olduğu bildirilmektedir (Ali ve ark., 2007;Safavi, 2015).…”
Section: Sarı Pasunclassified